Biochar: a potential route for recycling of phosphorus in agricultural residues. Issue 5 (30th April 2016) - Dai, Lichun; Li, Hong; Tan, Furong; Zhu, Nengmin; He, Mingxiong; Hu, Guoquan
Abstract: Phosphorus (P) is a finite and dwindling resource, while an enormous amount of P flows to agricultural residues with increasing agricultural production. Therefore, the recycling of P in agricultural residues is critical for P sustainability in agricultural systems, which is dominated by the route of direct land application. Biochar production from agricultural residues and its subsequent land application have been suggested as solutions for waste biomass disposal, carbon sequestration, soil amendment/remediation, and crop production promotion. However, little attention has been paid to the contrasting effects of the land application of biochar vs. agricultural residues on the recycling of P accumulated in agricultural residues. Phosphorus in agricultural residues can be retained and transformed into stable forms of P in the resulting biochar. Thus, compared to agricultural residues, biochar provides lower amounts of labile P and releases its P more slowly while providing a long‐lasting P source, and the loss potential of P from biochar is reduced by low mobility of its P, indicating that biochar‐based P recycling route could substantially promote P recycling by acting as sustainable P source and diminishing the loss of P applied to soil.